THE COMPETENCE OF MATHEMATICS TEACHERS IN THE DEVELOPMENT OF MATHEMATICAL COMPETENCE OF STUDENTS - Khatamov Khumoyun Isroilovich; Usmonov Isroiljon Mukhtorjon ugli; Alijonov Sirojiddin Husan ugli (American Journals, 2024)
Education cannot be distinguished from two main factors; teacher and student. Without both of these two factors, it is not actually education. Education in Uzbekistan is still far from expected. This can be seen from the presence of difficulties in achieving decent labor results in accordance with the educational level of graduates. One of the reasons for the low quality of education in Uzbekistan is that the qualifications of teachers as teachers are still considered low compared to the standards prepared. This article discusses the impact of teacher competence on student competence, particularly in the study of mathematics.
Keywords: mathematical competence, mathematics teachers, content knowledge, pedagogical skills, classroom management, assessment, problem-based learning, differentiated instruction, technology integration, mathematical modeling, professional development, collaborative educational ecosystem.